Statement of the ASPHER Task Force on War and Public Health on the Conflict in Israel/Palestine - Razum, Oliver (2024)
Razum, O., Barach, P., Bochenek, T., Cunningham, C., Davidovitch, N., Kostoulas, P., Lindert, J., Lopes, H., Prikazsky, V., Reid, J., Tiljak, M. K., & Middleton, J. (2024). Statement of the ASPHER Task Force on War and Public Health on the Conflict in Israel/Palestine. Public Health Reviews, 45, 1-2. https://doi.org/10.3389/phrs.2024.1607047